Rescue-i: An Intelligent Real Time Monitoring and Decision Making in Hazardous Environment - AHMAD, AZWIN HAZRINA (2018)
A real time physiology stress monitoring is crucial for fire-fighters since making accurate decision while performing hazardous work is almost impossible. Fast and accurate decision in this chaotic situation, such as, a rescue mission by fire-fighter in a fire scene will prevent harm, fatality and losses of belonging. In this thesis, an intelligent real time system named Rescue-i is proposed to analyse the physiology stress risk level of fire-fighters and automatically suggest the actions to be taken by the wearer. The core of this intelligent system is not only the hardware, but the software engine.